The Islamic View of Jesus and Its Implication for Muslim-Christian Harmony in Maluku - Jenny Abrahams (Program Pascasarjana UKIM, 2023)
This article aims to explore the views of several lecturers at the Islamic State Institution of Ambon (IAIN Ambon), Maluku, as representatives of Islamic academics towards Jesus. Interestingly, in the context of Maluku, the encounter between Christians and Muslims appears to be a dynamic relationship, manifested not only in forms of harmony and peace but also in tension, conflict, and even violence. Historically, religious-based conflicts and violence in 1999–2004 are evidence of the dynamic relationship between Muslims and Christians in Maluku. Further, the conflict that lasted for five years generally used certain religious symbols as media to provoke and mobilize each side in acts of violence. Then, it impacts various prejudices, mockery, and even hate speeches towards the central figures worshiped by each religion, such as Jesus and Muhammad. However, based on research through in-depth interviews with several lecturers of the Islamic State Institution of Ambon, Islamic theology has a positive view of Jesus, which can even become a meeting point as the basis for Islamic-Christian dialogue in Maluku, even though there are substantial differences with Christian theological views. Specifically, there are two main views: 1) Jesus as Ulil Azmi, and 2) Jesus as a role model of love and humanity. Thus, this paper can provide alternative views as a conceptual basis for creating and maintaining peaceful and harmonious Muslim-Christian relations in Maluku.